Malaysian Administrative Modernization and Management Planning Unit Sarawak Branch / Hamzani Fadil - Fadil, Hamzani (University Technology MARA Sarawak, 2014)
According to MAMPU Official Portal (www.mampu.gov.my), MAMPU was established based on the study conducted by Prof. John D. Montgomery and Milton J. Esman (1965), which is Development Administration in Malaysia. The study acknowledged the need to upgrade professionalism in the public service through educational and training programmes. Based on recommendations of the study, the Development Administrative Unit (DAU) was established in 1966 to spearhead administrative reforms in the Government (MAMPU Official Portal, www.mampu.gov.my). DAU was later expanded and renamed as Implementation Coordination Development Administrative Unit (ICDAU) where tasked with coordinating the planning and development of human resources. After that, ICDAU was later restructured due to the rapid and dynamic growth of the public service in 1977 (MAMPU Official Portal, www.mampu.gov.my). In 1986 according to MAMPU Official Portal (www.mampu.gov.my), the role of human resource planning was reassigned to other agencies so that the ICDAU can focus its efforts on public sector administrative modernization and management consultation and since that, it was known as the Malaysian Administrative Modernization and Management Planning Unit (MAMPU). Based on Jeong (2007), the Malaysian Administrative Modernisation and Management Planning Unit (MAMPU) whereby in Malay called as Unit Pemodenan Tadbirandan Perancangan Pengurusan Malaysia is one of the prominent government agencies in Malaysia that is responsible for modernizing and reforming the public sector. It is also one of the few central agencies in Malaysia who is responsible for modernizing and reforming the public sector in the areas of administrative reforms and it is placed under the Prime Minister Department. As the lead agency in public service transformation, MAMPU is responsible in improving the nation's competitiveness through the effective implementation of modernisation initiatives in organisational management and ICT in the Public Sector (MAMPU Official Portal, www.mampu.gov.my).